Molecular characterisation and tracking of severe acute respiratory syndrome coronavirus 2 in Thailand, 2020–2022 - Puenpa J. (2023)
The global COVID-19 pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was first detected in China in December 2019. To date, there have been approximately 3.4 million reported cases of COVID-19 and over 24,000 deaths in Thailand. In this study, we investigated the molecular characteristics and evolution of SARS-CoV-2 in Thailand from 2020 to 2022. Two hundred sixty-eight SARS-CoV-2 isolates, collected mostly in Bangkok from COVID-19 patients, were characterised by partial genome sequencing. Moreover, the viruses in 5,627 positive SARS-CoV-2 samples were identified as viral variants – B.1.1.7 (Alpha), B.1.617.2 (Delta), B.1.1.529 (Omicron/BA.1), or B.1.1.529 (Omicron/BA.2) – by multiplex real-time reverse transcription polymerase chain reaction (RT-PCR) assays. The results revealed that B.1.36.16 caused the predominant outbreak in the second wave (December 2020–January 2021), B.1.1.7 (Alpha) in the third wave (April–June 2021), B.1.617.2 (Delta) in the fourth wave (July–December 2021), and B.1.1.529 (Omicron) in the fifth wave (January–March 2022). The evolutionary rate of the viral genome was 2.60 × 10-3 (95% highest posterior density [HPD], 1.72 × 10-3 to 3.62 × 10-3) nucleotide substitutions per site per year. Continued molecular surveillance of SARS-CoV-2 is crucial for monitoring emerging variants with the potential to cause new COVID-19 outbreaks.